SINERGI STAKEHOLDER UNTUK KESEJAHTERAAN : Studi Kelompok Wanita Tani Sumber Patedhan Program CSR PT Pertamina (Persero) Integrated Terminal Cilacap - Erna Utami; Rahadiyand Aditya; Ardi Sugianto (UIN Sunan Kalijaga Yogyakarta, 2020)
The number of workers in the formal or informal sector is still dominated by men. One of the reasons is the discovery of patriarchal culture in several fields of life. The role of the government, non-governmental institutions as well as the private sector in breaking the chain needs to be done. So how is the synergy of stakeholders to get help through Sumber Patedhan RW 01 dan 03 Women's Farmers Group in Lomanis Cilacap Village? This research uses descriptive qualitative with data collection techniques using interviews and documentation. This research concludes that the CSR Program conducted by PT Pertamina Integrated Terminal Cilacap is included in the Corporate Citizenship category. This Program Has Cause Programs That The Company Has Done Tackling Society And Sustainability. Synergy stakeholders have also participated in this program. although there are a few notes. Keywords: Corporate Social Responsibility, Women's Empowerment, Women Farmers' Groups, Welfare, Stakeholders.